PEMBIAYAAN BAGI HASIL MUDHARABAH DAN PEMBIAYAAN BAGI HASIL MUSYARAKAH TERHADAP TOTAL ASET PADA BANK BRI SYARIAH PERIODE 2009-2020 - Afriyanti Harahap; Silviana Sri Wulandari; Delia Fitria Nurrohmah (Prodi Akuntansi, 2022)
This study aims to examine whether there is a relationship between mudharabah profit sharing financing and musyarakah profit sharing financing to the total assets of BRI Syariah Bank for the 2009-2020 period. The research method used in this research is descriptive quantitative. This type of research is an associative research conducted to test the hypothesis of previous research by describing the causal relationship between the independent variable and the dependent variable. The population in this study is financial statement data for the 12-year period 2009 to 2020 at BRI Syariah Bank. Based on the results of this study, it shows that the variable for partial mudharabah profit sharing with results of 0.816> 0.05 is larger which means it has no effect on total assets, and partial musyarakah profit sharing financing with results of 0.000 <0.05 is smaller, which means it has an effect on total assets. . Meanwhile, simultaneously, the variable of mudharabah profit-sharing financing and musyarakah profit-sharing financing with a result of 0.000 <0.05 is smaller, which means it has an effect on total assets.